ANALYSIS OF THE STUDENTS’ GEOMETRIC REASONING ABILITY - Andi Mariani Ramlan; Sri Muliana Ramlan (JME (Journal of Mathematics Education), 2017)
This research was a descriptive research with quantitative approach that aimed to analyze or describe the geometric reasoning ability of SMA Negeri 1 Wundulako students in solving mathematical problems related to the building of the three dimensions. Indicators used to describe students' geometric reasoning abilities include visualization, analysis, abstraction, and formal deduction. Data collection techniques consisted of interviews to deepen information about students 'geometric reasoning abilities and written tests to get an idea of students' cognitive abilities. Subjects in this study, namely students class XI.IA SMA Negeri 1 Wundulako as many as 40 students who have studied three dimensional materials. Data analysis in this research used descriptive analysis. Based on the data analysis obtained average value of 49.86, median 53.33, mode 66.67. The standard deviation was obtained at 22.39, it showed that there was a considerable difference of value between the students who mean in high ability category with the average of 91,11, medium ability category equal to 66,27, and low ability equal to 31,82 , With minimum value is 3.33 and maximum 93,33. In general, based on descriptive analysis, the geometric reasoning ability of SMA Negeri 1 Wundulako students was still low.